Entre saberes e práticas: a construção da identidade de professor de língua inglesa na formação inicial - Gandour, Deny de Souza (2013)
Within the field of Applied Linguistics, this study deals with issues related to teachers knowledge and the construction of professional identity in the context of initial teacher education process. The participants of the study belong to a group of student-teachers on the last phase of the English language and literature undergraduate course at the State University in Rio Grande do Norte (UERN). The theoretical concepts adopted in this research are those of identity, in their social, historical and cultural perspectives which emphasize its instable, multifaceted and fluid character and which are primary proposed by S. Hall, A. Giddens as well as the studies on professional identity held by C. Dubar. The general objective is to analyze the English language teacher education process at UERN, seeking to explain the relations between the construction of professional identity and the construction of knowledge and competences necessary to a critical and reflexive teacher education. Among the items that compose the frame of practices and knowledge that outline the educator profession, the study also considered the proposals of the reflexive practitioner by D. Schön and his followers, as well as the critical reflection perspectives stated by P. Freire, H. Giroux, among others. The procedures of investigation followed an approach based on the qualitative paradigm including the analysis of a corpus consisted of empirical data constructed by means of semi-structured interviews conducted in on-line virtual environment. The analysis revealed that the professional identity traits, although they might also come from former experiences, concerning the initial education process, they are mainly built from experiences in socializations spaces concerning both knowledge acquisition processes and reflection on teaching processes. It is pointed out a tridimensional relation evolving reflection on teaching, teacher knowledge acquisition and construction of professional identity process. It is also emphasized that this tridimensional relation must be seen as inseparable items, considering that these processes boost themselves mutually in the teachers’ initial education process.